Acthar Gel (RCI): A Narrative Literature Review of Clinical and Economic Evidence - Wan GJ; Niewoehner J; Hayes K (Dove Medical Press, 2023)
George J Wan, John Niewoehner, Kyle Hayes Mallinckrodt Pharmaceuticals, Bridgewater, NJ, USACorrespondence: George J Wan, Mallinckrodt Pharmaceuticals, 440 Route 22 East, Bridgewater, NJ, 08807, USA, Tel +1 (908) 238-6600, Email George.Wan@mnk.comAbstract: Acthar® Gel (repository corticotropin injection [RCI]) is a naturally sourced complex mixture of adrenocorticotropic hormone analogs and other pituitary peptides used to treat patients with serious and rare inflammatory and autoimmune conditions. This narrative review summarizes the key clinical and economic findings among 9 indications: infantile spasms (IS), multiple sclerosis (MS) relapses, rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), dermatomyositis and polymyositis (DM/PM), ocular inflammatory diseases (primarily uveitis and severe keratitis), symptomatic sarcoidosis, and proteinuria in nephrotic syndrome (NS). Key studies of clinical efficacy and healthcare resource utilization and cost from 1956 to 2022 are discussed. Evidence supports the efficacy of RCI across all 9 indications. RCI is recommended as first-line treatment for IS and is associated with improved outcomes for the other 8 indications, including increased recovery rates in MS relapse; improved disease control in RA, SLE, and DM/PM; real-world effectiveness in patients with uveitis and severe keratitis; improved lung function and reduced corticosteroid use in symptomatic sarcoidosis; and increased rates of partial remission of proteinuria in NS. For many indications, RCI may improve clinical outcomes during exacerbations or when conventional treatments have failed to show a benefit. RCI is also associated with a reduction in the use of biologics, corticosteroids, and disease-modifying antirheumatic drugs. Economic data suggest RCI is a cost-effective, value-based treatment option for MS relapse, RA, and SLE. Other economic benefits have been demonstrated for IS, MS relapses, RA, SLE, and DM/PM, including reduced hospitalizations, lengths of stay, inpatient and outpatient services, and emergency department visits. RCI is considered safe and effective and features economic benefits for numerous indications. Its ability to control relapse and disease activity makes RCI an important nonsteroid treatment option that could help preserve functioning and well-being among patients with inflammatory and autoimmune conditions.Keywords: dermatomyositis and polymyositis, multiple sclerosis relapse, nephrotic syndrome, rheumatoid arthritis, sarcoidosis, systemic lupus erythematosus